عبد الكريم سروش ونظريته حول الوحي = Abdul Karīm Surūsh and his Theory about revelation - Elatrash, Radwan Jamal Yousef; Obaid, Sayed Obaidullah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يتناول هذا البحث ترجمة عبد الكريم سروش الإيراني، الرائد الحقيقي للحداثيين في أوساط المثقفين الناطقين باللغة الفارسية، حيث كان له موقف فكري من الإسلام بشكل عام جعله لصيقاً بالأفكار الحداثية الجديدة، إذ كان له نظريته الخاصّة الجديدة حول الوحي، حيث أنه جعل يشكك في مصدرية القرآن ونسبه إلى النبي ﷺ، فجعل ألفاظ القرآن من النبي ﷺ والمعنى من الله عزّ وجلّ، وجعل النبي ﷺ شاعراً خلقه الله وعلّمه وربّاه أحسن تربية، فالنبي ﷺ عنده بشرٌ يجري عليه ما يجري على البشر، فهو يخطئ ويتأثّر ببيئته وظروفه. وعليه فإنّ البحث يدرس هذه النظرية ويحلّلها، وينقدها وينفدها، مستعيناً بالأدلّة الشرعية والعقليّة، حيث أثبت أن لفظ القرآن ومعناه من الله تعالى، وهذا ما أجمع عليه المسلمون قديماً وحديثاً. وطبيعة هذا البحث يقتضي أن يتمّ الاعتماد على المنهجين الاستقرائي والتحليلي من أجل الوصول إلى نتائج مرضية. ********************************************************** This research presents the biography of Abdul Karīm Surūsh, the Iranian pioneer for modernists among the Persian spoken intellectuals, where he had his viewpoint toward Islam in general, it made him connected to the ideas of new modernism. Since he had stated his new specific theory regarding the revelation, he brought up some doubts to Qur'ān as a real source, and he attributed it to the prophet, which he says that the words of Qur'ān came from prophet, but its concepts and meaning came from Allah, and he made the prophet a poet who has been created, taught and raised by Allah. For him the prophet is a man just like other people, so he makes mistakes and being affected by his environment and circumstances. Therefore, this research elaborates, analyzes and obliterates this theory, based on the religious and rational reasons, proves that both the words and the meaning of Qur'ān come from Allah, and it is that all early and nowadays Muslims are unified on it. The nature of this research requires that both inductive and analytical approaches should be adopted to achieve acceptable results.